Men's health care: concept analysis - Reis de Sousa, Anderson; de Carvalho Félix, Nuno Damácio; Rosendo da Silva, Richardson Augusto; de Santana Carvalho, Evanilda Souza; Pereira, Álvaro (Investigación y Educación en Enfermería, 2023)
Objective. To analyze the concept of men's health care and identify its essential, antecedent and consequent attributes in the health context. Methods. This is a concept analysis structured in the theoretical-methodological framework of the Walker and Avant Model. An integrative review was carried out between May and July 2020, using keywords and descriptors: Men's Care and Health. Results. The concept of men's health care is structured by 240 attributes, 14 categories, 82 antecedents and 159 consequents, from the selection of 26 published manuscripts. The design was evidenced from the dimensions: Intrapersonal, psychological and behavioral related to masculinities, interpersonal, organizational and structural, ecological, ethnoracial, cross-cultural and transpersonal. Conclusion. The concept of men's health care revealed the male specificities regarding the recognition of the place of health care and the daily exercise in the lived experience.